APAKAH IKLAN DALAM BENTUK TV ADVERTISING MASIH CUKUP EFEKTIF UNTUK DIGUNAKAN DI ERA DIGITAL MEDIA? - Debora Garcia (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2015)
Advertisement is a kind of communication between the company and thecustomers. Advertisement isn’t only useful for the company as a promotion media, butalso useful for the customers as an information media about the products. A fewdecades ago, TV is the most favorite media that is used as a promotion media becauseTV is an entertainment and information media that can reach people widely. However,in the emerging digital age at this time, TV is considered to be less effective to be madeas an advertising media because its segments are too wide and then it will affect on theexpensive advertising cost. Nowadays, the companies prefer to turn to the internet tocreate online advertising because of the characteristics of online advertising that areconsidered more effective for advertising such as clearer segmentation, loweradvertising rates, and more interactive.